Joyfull Learning pada Pembelajaran Pendidikan Agama Kristen Kelas 1 SD - Purba, Sudiarjo (STT Internasional Harvest Tangerang, 2025)
Christian Religious Education teachers must understand that first-grade elementary school students face a challenging period in their growth and development, both academically, psychologically, and spiritually. As new students at the beginning of the school year, they will encounter new things in the classroom, which requires the support of a joyful learning atmosphere. New students in a class at the beginning of the school year are not equally prepared, both for the classroom conditions and the teaching materials they will receive. This article aims to provide insight to Christian Religious Education teachers in understanding the conditions of first-grade students; develop Christian Religious Education teachers' knowledge in connecting the conditions of first-grade students with the readiness of Christian Religious Education teachers and presenting in-depth learning; and strengthening joyful learning in Christian Religious Education learning in first-grade elementary school. The findings of the study are the importance of implementing joyful learning in Christian Religious Education learning in first-grade as part of in-depth learning. The conclusion obtained is: joyful learning can build a more conducive learning atmosphere in Christian Religious Education learning in first-grade